2006
DOI: 10.1021/op068011l
|View full text |Cite
|
Sign up to set email alerts
|

Safe Handling of Boranes at Scale

Abstract: The safe handling of borane complexes and alkylboranes (trialkylboranes, dialkylboranes, and trialkylborohydride reagents) and related workup issues are addressed. Oxidation of alkylboranes and quenching of reaction mixtures to safely decompose the reagent or products are discussed. Several case studies demonstrate large-scale applications of borane reagents for carboxylic acid reduction, reductive amination, and hydroboration followed by oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…Although many borohydride reagents are relatively stable solids, their contact with moisture can cause decomposition with the release of hydrogen gas. Therefore, appropriate precautions are required for larger scale reactions as well as during transport and storage [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Although many borohydride reagents are relatively stable solids, their contact with moisture can cause decomposition with the release of hydrogen gas. Therefore, appropriate precautions are required for larger scale reactions as well as during transport and storage [5]. …”
Section: Introductionmentioning
confidence: 99%
“…1 3,4-Difluoro-2-methylbenzoic Acid (15). A 50 L jacketed reactor was flushed with nitrogen and charged with magnesium turnings (852 g, 35 mol) followed by a few crystals of iodine (0.2 g) and 2-methyltetrahydrofuran (2-MeTHF) (20 L).…”
Section: Methodsmentioning
confidence: 99%
“…Care was taken not to heat the reaction mixture in order to eliminate the risk of formation of diborane. 15 When the imide had been completely consumed, methanol was added slowly over a period of 16−24 h to ensure that the liberated hydrogen was efficiently removed. Calorimetric evaluation ( Figure 5) showed that the hydrogen evolution was mostly complete after the addition of the first 10% of the charge of the methanol and was generally controlled by the rate of addition ( Figure 6).…”
Section: Imide-based Synthesis Of Bromobenzoxazepinementioning
confidence: 99%
“…The Schiff base and aminoalcohol ligands were synthesized according to known literature procedures [7,8]. 3-(adamantan-1-yl)-3,4-dihydro-2H-benzo[e] [1,3,2]oxazaborinane (1a) H3B·SMe2 (2.6 mL of a 2 M toluene solution, 5.2 mmol) was added dropwise to a stirred solution of 2- ((adamantan-1-ylamino)methyl)phenol (1.22 g, 4.73 mmol) in toluene (2 mL). Gas evolved upon addition of the borane and a white precipitate formed.…”
Section: Generalmentioning
confidence: 99%
“…The resulting organoboron products are remarkably versatile synthons that can be transformed into diverse families of important compounds (Figure 1). However, difficulties associated with synthesis, cost, handling and storage of hydroboranes have continued to plague their practical use at an industrial scale [2]. As such, there has been a considerable amount of research addressed at synthesizing novel boranes for the hydroboration reaction [3].…”
Section: Introductionmentioning
confidence: 99%